PSVI-8 Effects of feeding ensiled or dried grape pomace on measures of nitrogen utilization in backgrounding cattle. (30th November 2020) - Chibisa, Gwinyai E; Ream, Cody; Stevens, Allison
Abstract: Because of its content of polyphenolic compounds, feeding grape pomace (GP) could alter nitrogen (N) utilization in cattle in a manner that limits urinary N excretion and, thus, reactive N emissions. However, the preservation method used for GP, whose shelf-life is limited when fresh, could potentially cause changes in the bioactivity of the polyphenolic compounds. This study evaluated the effects of feeding either ensiled or sun-dried GP on ruminal ammonia-N (NH3 -N) and plasma urea-N (PUN) concentrations, and route of N excretion in backgrounding cattle. Six ruminally-cannulated beef heifers were used in a replicated 3 × 3 Latin square design with 21-d periods. Dietary treatments were (DM basis): 1) a typical backgrounding diet (CON), 2) CON + 15% ensiled GP, and 3) CON + 15% sun-dried GP. Grape pomace partially replaced triticale silage in the diet. Ruminal fluid (d 19 at 3 h post-feeding), blood (d 21 at 3 h post-feeding), and fecal grab and spot urine samples (d 19 at 0900, 1500, and 2100; d 20 at 0300, 1200, and 1800 h; d 21 at 0000 and 0600 h) were collected and analyzed for metabolites. Data was analyzed using PROC MIXED in SAS. There was no diet effect (P ≥ 0.48) on N intake, and ruminal NH3 -N and PUN concentrations. Urine N (g/d and % of N intake) and urea-N (g/d) output were lower (P < 0.01) for heifers fed GP-containing diets than the CON diet. However, fecal N excretion (g/d and % of N intake) was greater (P = 0.01) for heifers fed GP-containing diets than the CON diet. In summary, although there was no diet effect ruminal NH3 -N and PUN concentrations, feeding GP irrespective of preservation method, was effective in changing the route of N excretion from urine to feces, which is beneficial from an environmental standpoint.